2019
DOI: 10.3389/fphar.2019.00615
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Hepcidin in Polymicrobial Sepsis and Acute Kidney Injury

Abstract: Background: Acute kidney injury (AKI) portends worse prognosis following sepsis, with limited available interventions. Host iron acquisition by pathogens and systemic inflammatory response are key events in the pathogenesis of sepsis. In sepsis, hepcidin induces iron sequestration to limit iron availability to pathogens. Hepcidin is also known to limit inflammation. Since its role in pathophysiology of sepsis-associated AKI is unknown, we investigated the effect of exogenous hepcidin in endotoxin- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Interestingly, pretreatment of mice with hepcidin also protects against SA-AKI and mortality. Hepcidin mediated macrophage iron retention and consequently increased FtH expression [8].…”
Section: Ferritin Light Chain In Sepsis-aki 617mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, pretreatment of mice with hepcidin also protects against SA-AKI and mortality. Hepcidin mediated macrophage iron retention and consequently increased FtH expression [8].…”
Section: Ferritin Light Chain In Sepsis-aki 617mentioning
confidence: 99%
“…Interestingly, pretreatment of mice with hepcidin also protects against SA-AKI and mortality. Hepcidin mediated macrophage iron retention and consequently increased FtH expression [8]. Several studies have demonstrated that iron chelation prior to induction of AKI is protective (Table 1); however, the effect of iron chelators following established renal injury is not well studied.…”
Section: Impact Of Regulating Iron Levels During Sepsismentioning
confidence: 99%
“…Multiple organ dysfunction and circulatory failure in sepsis are caused by systemic inflammation after exposure to LPS 39,40 . As the largest immune organ, the spleen plays an important role during LPS‐induced systemic inflammation 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It reduces extracellular iron levels through downregulating iron absorption in duodenal and ferroportin expression and cellular iron release in macrophages [18,20]. And the protective role of hepcidin in AKI provides evidence on the key role of iron in mediating AKI [21]. Meanwhile, a study involving 807 patients showed that plasm catalytic iron and hepcidin possibly be useful prognostic indicators in AKI patients [9].…”
Section: Discussionmentioning
confidence: 99%